2008
DOI: 10.4319/lo.2008.53.3.0986
|View full text |Cite
|
Sign up to set email alerts
|

In situ fluxes of dissolved inorganic nitrogen from the sponge community on Conch Reef, Key Largo, Florida

Abstract: We measured ammonium and nitrate plus nitrite fluxes from 14 common sponge species on a Florida Keys reef (Conch Reef) using a combination of incubation experiments and an in situ method that requires no manipulation of the sponge. On a 600-m 2 section of Conch Reef, species-specific biomass for all nonencrusting sponges was measured. The biomass data combined with species-specific dissolved inorganic nitrogen (DIN) flux rates yielded the benthic DIN flux from 14 species, and allowed us to extrapolate these da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
221
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(242 citation statements)
references
References 40 publications
18
221
3
Order By: Relevance
“…Recent work has demonstrated the potential for sponges to consume both DOC and bacterioplankton at biogeochemically significant rates (Yahel et al, 2003;Van Duyl et al, 2006;de Goeij and Van Duyl, 2007;De Goeij et al, 2008). However, conspicuous sponge taxa, which exhibit the highest filtration rates (Southwell et al, 2008), are virtually absent from our study area, and even inconspicuous benthic sponges cover o1% of the reef benthos in Moorea on average (Adjeroud, 1997, http://mcr. lternet.edu/data/), although cryptic coelobite communities can increase reef surface area sevenfold and rapidly remove both DOC and bacterioplankton (Richter et al, 2001;Scheffers et al, 2004;de Goeij and Van Duyl, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…Recent work has demonstrated the potential for sponges to consume both DOC and bacterioplankton at biogeochemically significant rates (Yahel et al, 2003;Van Duyl et al, 2006;de Goeij and Van Duyl, 2007;De Goeij et al, 2008). However, conspicuous sponge taxa, which exhibit the highest filtration rates (Southwell et al, 2008), are virtually absent from our study area, and even inconspicuous benthic sponges cover o1% of the reef benthos in Moorea on average (Adjeroud, 1997, http://mcr. lternet.edu/data/), although cryptic coelobite communities can increase reef surface area sevenfold and rapidly remove both DOC and bacterioplankton (Richter et al, 2001;Scheffers et al, 2004;de Goeij and Van Duyl, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…In coral reef waters, observations of high nitrite/nitrate concentrations compared to adjacent, open water habitats have long suggested active nitrification among reefassociated microbes (Webb et al, 1975). More recent studies have reported that host-associated microbes in sponges and corals contributed to nitrification in these reef habitats to a larger extent than reported for free-living communities in sediments and seawater (Diaz and Ward, 1997;Southwell et al, 2008). The finding herein of widespread ammonia-oxidizing archaea in coral reef ascidians suggests an additional and potentially important source of nitrification in reef habitats.…”
Section: Discussionmentioning
confidence: 85%
“…This similarity indicates that the composition of nutrients in the water column was closely related with 10 biological processes during both tidal periods, but the biological effect appeared to be less during the spring tide as inferred from the less significant correlations. The net release of nutrients during the neap tide with a very Redfield-like ratio suggests that the net nutrient fluxes in this system were likely to be dominated by the uptake and remineralization of plankton/oceanic organic particles by benthic filter feeders as observed in other reefs (e.g., Ayukai, 1995;Ribes et al, 2005;Southwell et al, 2008;Genin et al, 2009;Monismith et al, 2010). The net uptake of nitrate and phosphate was mainly made 15 by reef primary producers.…”
Section: The Generation and Consumption Of Nomentioning
confidence: 99%